Intussusception as an unusual etiology of intestinal obstruction in adults: case report and review - Campa , Kassandra Janeth Espinal; Arias, Francisco de Jesús Cisneros; Campa , Alondra Yaneli Espinal; Vega, Hector Aurelio Diarte (International Journal of Research in Medical Sciences, 2023)
Intussusception is a rare entity in adults, representing 1 to 5 percent of cases of intestinal obstruction. The clinical manifestations are non-specific, a structural lesion is identified by imaging, in more than 70% of the cases. Most cases require surgical treatment. We report the case of a 65-year-old female patient, with a history of intermittent colicky abdominal pain of two months of evolution, associated with nausea, vomiting, melena, and weight loss. Assessed in the emergency department due to worsening abdominal pain and lack of defecation. Her laboratory data reported anemia and leukocytosis. Abdominopelvic CT scan reported an image compatible with intussusception. We performed an emergency exploratory laparotomy, finding the terminal ileum invaginated into the colonic lumen., caused by a gastrointestinal stromal tumor. Intussusception in adults is uncommon but it should be considered as a diagnostic possibility in patients with intestinal obstruction, intestinal bleeding, and a palpable abdominal mass. Although these are non-specific manifestations, complementing the study with chemical and imaging analyzes significantly increases the diagnostic probability. The set of data obtained should be used to select the most appropriate treatment.